(untitled) (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2021)
This paper tries to look at traditional medicine in an anthropological perspective. Based on the facts that occur in the community, as a whole it can be said that the traditional medical system is a socio-cultural phenomenon. The practice of traditional medicine is then also attracting the attention of anthropologists to examine more deeply about the traditional treatment system from the perspective of local communities. The field of anthropology calls it the term ethnomedicine, which refers to traditional medical practices related to cultural interpretations of health, illness, illness, ways of handling and healing practices.